Capacity Improvement in Low Voltage Relay aided PLC based on Decode and Forward Protocol over Middleton class-A Channel. Issue 4 (4th July 2021) - Khyari, N.; Khalfallah, S.; Barouni, Y.; Ben Hadj Slama, J.
Abstract : We are adopting, in the present work, a cooperative transmission procedure for an in-home communication system as a solution to meet the contemporary needs of the smart grids and smart home. It is composed of a Low Voltage PL channel assisted by a relay station in the presence of an impulsive noise. Our contribution consists of using the Decode and Forward (DF) relaying protocol while adapting the Joint Modulation (JM) technique to the PLC context. The benefits of this integration are highlighted in a comparative study of the system capacities using the DF-JM and the Amplify and Forward (AF) relaying protocols. The transmission channel is affected by an impulsive noise of type Middleton class-A. The evaluation is based initially on signal attenuation model and eventually on Transmission Line Theory. For the latter, a multi-branched cable with loads at the ends is considered when keeping the relay at the optimal selected position. Simulations and mathematical proofs show that the DF JM relaying technique offers more capacity over the AF independently of cable configuration. Furthermore, in the current study, we analyse the effect of load impedance and branch density on the DF-JM PLC as well as their contribution to the system performance while varying the class-A model parameters.